Real-time observation of phase coexistence and a1/a2 to flux-closure domain transformation in ferroelectric films. (July 2020) - Ma, J.Y.; Wang, Y.J.; Zhu, Y.L.; Tang, Y.L.; Han, M.J.; Zou, M.J.; Feng, Y.P.; Zhang, N.B.; Geng, W.R.; Wu, B.; Hu, W.T.; Guo, X.W.; et al.
Abstract: Phase coexistence in ferroelectric oxide films displays complex phase competitions and transformation which suggest new multiple-coupled properties. Here we have successfully engineered the coexistence of flux-closure and a1 /a2 phases in tensile-strained PbTiO3 films sandwiched between GdScO3 substrate and a SrTiO3 layer. Moreover, by using in-situ electron beam illumination, the unusual transformation from a1 /a2 phase to the flux-closure phase was directly observed. In detail, there are two types of transformations: One is the nucleation, growth, and expansion of the flux-closure phase from the internal region of the a1 /a2 phase. The other feature is a "dislocation gliding" like behavior: a thin lamella of a1 /a2 shrinks like "partial dislocation pairs" and finally the gradually disappeared a1 /a2 lamella forms a "perfect dislocation" in the flux-closure domain matrix. Phase-field simulations suggest that the a1 /a2 to flux-closure transition is induced by the decrease of the depolarization field, which is screened by the injected electrons from electron beam irradiation. These results directly confirm the phase interconversion under an external stimulus at the nanometer scale, which shed new light on the fabrication of new polar textures. Graphical abstract: Image, graphical abstract